IMPLEMENTASI ETNOMATEMATIKA BERBASIS BUDAYA LOKAL GUNUNGKIDUL TRADISI GUMBREGAN PADA MATERI BANGUN RUANG - Anik Dwi Nurmawati; Budi Artopo (Delta: Jurnal Ilmiah Pendidikan Matematika, 2022)
This study aims to overcome problems in learning Mathematics. The goal is that Mathematics learning can be more adapted to the cultural context of students and society, and Mathematics can be more easily understood because it is no longer perceived as something 'foreign' by students and society. Mathematics learning really needs to provide content/bridging between Mathematics in the everyday world based on local culture and school Mathematics. The implementation of ethnomathematics based on the Gumbregan tradition of Gunungkidul culture in building materials was carried out on fifth grade students of SDN Baran I, Gunungkidul in learning activities for Mathematics subject for grade V for the academic year 2021/2022. The subjects were fifth graders at SDN Baran I Rongkop, with a total of 22 students, consisting of 9 male students and 13 female students. The implementation of ethnomathematical learning based on the local culture of Gunungkidul, the Gumbregan tradition in building materials, can increase students' activeness and enthusiasm in the Mathematics subject of class V SDN Baran I. Students can recognize and preserve the local culture of the Gunungkidul region, namely the Gumbregan tradition.